2016
DOI: 10.9745/ghsp-d-15-00234
|View full text |Cite
|
Sign up to set email alerts
|

Is Household Wealth Associated With Use of Long-Acting Reversible and Permanent Methods of Contraception? A Multi-Country Analysis

Abstract: In general, across the developing world, wealthier women are more likely than poorer women to use long-acting and permanent methods of contraception instead of short-acting methods. Exceptions are Bangladesh, India, and possibly Haiti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 20 publications
6
30
1
1
Order By: Relevance
“…This may reflect a different policy environment in the mentioned countries than other countries (13).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This may reflect a different policy environment in the mentioned countries than other countries (13).…”
Section: Discussionmentioning
confidence: 93%
“…IUD appears to be effective for at least 12 years and implants from 3 to 7 years (10,11). The benefits of LAPMs include convenience, high efficacy, costeffectiveness, time, effort, and money saving along with other potential health benefits (12,13). Despite these advantages, using LAPMs may lead to delayed childbearing or other undesirable outcomes (9).…”
Section: Introductionmentioning
confidence: 99%
“…Poor health infrastructure, lack of trained providers and contraceptive commodities, financial barriers, and community opposition to family planning can all impede access to modern contraceptives. [4] Prior research shows that wealth can contribute to significant inequities in access and uptake of long-acting and permanent method (LAPM) contraceptives [5], but these studies have not included messaging exposure, sexual and reproductive health indicators, or normative indicators that drive family size and fertility choices. Also, structural and cultural barriers to effective contraceptive use may also be exacerbated for adolescents living in rural areas, and limitations may be particularly acute for those who are unmarried and/or nulliparous.…”
Section: Introductionmentioning
confidence: 99%
“…This extends to decisions to seek FP services, from whom, and what methods to use. A study by Ugaz et al (2016) found that, in 17 of 30 countries, a greater proportion of poorer women used short-acting methods over long-acting methods than wealthier women, suggesting that financial barriers may suppress choice. For adolescents, cost may deter them from accessing health services altogether, more so than adults.…”
Section: Quality and Fp Purchasingmentioning
confidence: 99%